Sistem Pendukung Keputusan Menentukan Media Yang Tepat Untuk Pembelajaran Secara Online Di SMP Negeri 1 Alasa Talumuzoi Menggunakan Metode AHP - Kristiani Hulu; Arjon Sitio (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
In the world of education, we really need media as a means of interaction between teachers and students to convey information messages in teaching both in the form of written media, image media, sound media, video media, and print media. With the media, students are easier to understand and understand the meaning of the lessons given. The criteria data for the application of the Analytical Hierarchy Process (AHP) method include Ease of Access, Internet Quota Usage, Audio and Visual Interaction, User Limit Capacity, and Access Time Limit. Alternative data for the application of the Analytical Hierarchy Process (AHP) method includes 5 online media, namely Google Classroom, Edmodo Application, Zoom Meeting, Cisco Webex, and Moodle Application. The ranking results on the alternative obtained rank 1, namely Google Classroom Value = 0.4139. The system is designed web-based using PHP and MySQL.